Numerical evaluation of dissimilar cohesive models to predict the behavior of Double-Cantilever Beam specimens - Fernandes, R.L. (2017)
Adhesive bonding is a widely used joining method in industries such as aerospace, aeronautical and automotive because of specific advantages compared to the traditional fastening methods. Numerical approaches for the damage simulation of bonded joints based on fracture mechanics usually rely on Cohesive Zone Models (CZM). CZM suppose the characterization of the CZM laws in tension and shear, which are combined in mixed-mode criteria to predict the strength of bonded joints. This work evaluated the tensile fracture toughness (Gm) and CZM laws of bonded joints for two adhesives with distinct ductility. The Double-Cantilever Beam (DCB) test was used. The experimental work consisted of the tensile fracture characterization by the J-integral technique. A digital image correlation method was used for the evaluation of the tensile relative displacement (delta(n)) of the adhesive layer at the crack tip. Finite Element (FE) simulations were carried out to assess the accuracy of triangular, trapezoidal and linear-exponential CZM laws in predicting the experimental behaviour of the DCB tests. As output of this work, information regarding the applicability of these CZM laws to each type of adhesive is provided, allowing the subsequent strength prediction of bonded joints.